2005
DOI: 10.1128/jvi.79.9.5774-5785.2005
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor Class B Type I and Hepatitis C Virus Infection of Primary Tupaia Hepatocytes

Abstract: Hepatitis C virus (HCV) isHepatitis C virus (HCV) is a major cause of posttransfusion and community-acquired hepatitis in the world (8,24,25). The majority of HCV-infected individuals develop chronic hepatitis that may progress to liver cirrhosis and hepatocellular carcinoma (15). Treatment options for chronic HCV infection are limited, and a vaccine to prevent HCV infection is not available (11,15,17).HCV has been classified in a separate genus (Hepacivirus) of the Flaviviridae family. The virion contains a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 50 publications
(86 reference statements)
2
55
0
1
Order By: Relevance
“…To analyze the specificity of the produced anti-SR-BI polyclonal serum, CHO cells were transfected with pcDNA (control vector) or pcDNA SR-BI using liposome-mediated gene transfer (Lipofectamine; Invitrogen, Karlsruhe, Germany) according to the manufacturer's protocol. CHO cells were then incubated with anti-SR-BI polyclonal serum or preimmune control serum and analyzed for cell surface SR-BI expression by flow cytometry as described previously (7). Huh-7 cells (5 ϫ 10 3 /well) were seeded into 96-well plates (Corning Inc., Corning, NY), and the following day, cells were incubated with dilutions of antibodies specific for SR-BI or CD81 (5A6 clone; a gift from Shoshana Levy, Stanford University, Stanford, CA) for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the specificity of the produced anti-SR-BI polyclonal serum, CHO cells were transfected with pcDNA (control vector) or pcDNA SR-BI using liposome-mediated gene transfer (Lipofectamine; Invitrogen, Karlsruhe, Germany) according to the manufacturer's protocol. CHO cells were then incubated with anti-SR-BI polyclonal serum or preimmune control serum and analyzed for cell surface SR-BI expression by flow cytometry as described previously (7). Huh-7 cells (5 ϫ 10 3 /well) were seeded into 96-well plates (Corning Inc., Corning, NY), and the following day, cells were incubated with dilutions of antibodies specific for SR-BI or CD81 (5A6 clone; a gift from Shoshana Levy, Stanford University, Stanford, CA) for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The roles of CD81 and SR-BI as HCVpp receptors are well documented (2,7,9,11,39,68,91), and CD81 was recently shown to be required for cell culture-derived HCV infection (47,85,89,92). However, the extent to which SR-BI is required for HCV infection and whether it functions cooperatively with CD81 are poorly understood.…”
mentioning
confidence: 99%
“…Taken together, these results indicate that although CD81 may play a functional role as a co-factor for entry of HCV into PTHs, it is likely that other or additional molecules besides CD81 play a key role in HCV entry into PTHs. These may include other identified HCV host factors including SR-BI [27] or Claudin-1 [30] . Alternatively, other not yet identified host entry factors may mediate HCV-PTH interaction.…”
Section: Issnmentioning
confidence: 99%
“…Recently, a novel in vitro cell culture model system has been established for HCV with primary tupaia hepatocytes (PTHs) [25][26][27] . Using this cell culture system, we found that HCV E2 protein binding to PTHs and infection of PTHs with HCV could not be blocked with soluble CD81 and anti-CD81 [25] .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Whereas the exact mechanism of viral entry is unknown, mounting evidence indicates that CD81 and SR-BI are key molecules. 2,[4][5][6][11][12][13][14] In an infected individual, HCV exists as a viral quasispecies. 15 HCV can be classified into at least six major genotypes that exhibit extensive genetic variability, particularly in E1 and E2.…”
mentioning
confidence: 99%